Spirometric and morphological indicators of top level handball - Rogulj, N.; Marinovic, M.; Foretic, N.; Srhoj, V.; Herceg, Z. (Acta Kinesiologica, 2014)
The aim of this study was to determine the differences and relations of the morphological and spirometry characteristics between elite and the first league quality handball players. The study was conducted on the sample of 35 handball players playing in two clubs of 1st Croatian handball league divided in two groups: national team players (n=15) and the first league quality players (n=20). A total of 18 variables were analysed, 12 out of which to evaluate morphological characteristics and 6 to assess spirometry and ventilation parametres. Generally, by applying variance and discriminant analysis, no statistically significant differences between elite and high-quality players were established in the analysed areas. Individually, statistically significant differences are present only in the shoulder girth and hand length, and spirometry indicators show no statistically significant differences. Relation analysis between morphological and spirometry indicators detected positive statistically significant connections between most of the variables in the spirometry domain and in most of the longitudinal dimensionality skeleton variables as well as shoulder girth.